2014
DOI: 10.1177/1756283x14525250
|View full text |Cite
|
Sign up to set email alerts
|

Colonic smooth muscle cells and colonic motility patterns as a target for irritable bowel syndrome therapy: mechanisms of action of otilonium bromide

Abstract: Otilonium bromide (OB) is a spasmolytic compound of the family of quaternary ammonium derivatives and has been successfully used in the treatment of patients with irritable bowel syndrome (IBS) due to its specific pharmacodynamic effects on motility patterns in the human colon and the contractility of colonic smooth muscle cells. This article examines how. OB inhibits the main patterns of human sigmoid motility in vitro, which are spontaneous rhythmic phasic contractions, smooth muscle tone, contractions induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The reduced expression of myenteric SP likely affects both sensory perception and motility of the colon. As both afferent signaling and contractility have been implicated in the action of OB, our observations further expand the current knowledge by identifying potential mechanisms involved at the level of myenteric plexus.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The reduced expression of myenteric SP likely affects both sensory perception and motility of the colon. As both afferent signaling and contractility have been implicated in the action of OB, our observations further expand the current knowledge by identifying potential mechanisms involved at the level of myenteric plexus.…”
Section: Discussionsupporting
confidence: 58%
“…Nitric oxide acts directly on the intestinal smooth muscle cells causing relaxation and on enteric neurons or ICC modifying neurotransmission and attenuating release of excitatory neurotransmitters such as SP and acetylcholine . Substance P, NK1/2 receptors, and NO have been implicated in IBS or experimental models of this disorder, and they are potential targets for OB …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been addressed to identify the OB molecular targets . The results obtained in in vitro experiments after acute exposition of rat colonic strips to the drug showed that OB behaves as antagonist of the L‐type Ca 2+ channel, M2 and neurokinin receptors . These effects were considered the consequence of the OB interaction with the colonic smooth muscle cells because of the very poor systemic absorption of the drug .…”
Section: Discussionmentioning
confidence: 99%
“…The OB spasmolytic activity is mainly because of the interference of calcium influx through L‐type Ca 2+ channels and the mobilization of cellular calcium required for smooth muscle contraction, thereby limiting excessive intestinal contractility. Otilonium bromide also inhibits T‐type Ca 2+ channels and muscarinic and tachykinin receptors (NK1r and NK2r) on smooth muscle and primary afferent neurons that may have the joint effect of reducing motility and abdominal pain . Indeed, in strips of human colon, exposure to OB, either alone or in the presence of the tachykinin agonist, caused a concentration‐dependent reduction in the number of the cells that internalized the receptor NK2r .…”
Section: Introductionmentioning
confidence: 99%